2018
DOI: 10.30723/ijp.v16i36.22
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gold nanoparticles on WO3 thin film

Abstract: Chemical spray pyrolysis technique was used at substrate temperature 250 ˚C with annealing temperature at 400 ˚C (for 1hour) to deposition tungsten oxide thin film with different doping concentration of Au nanoparticle (0, 10, 20, 30 and 40)% wt. on glass substrate with thickness about 100 nm. The structural, optical properties were investigated. The X-ray diffraction shows that the films at substrate temperature (250 ˚C) was amorphous while at annealing temperature have a polycrystalline structure with the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
3
5
0
Order By: Relevance
“…The results showed that the films were amorphous. This result agrees with Myong et al [12] and with Ayat et al [13]. The XRD pattern showed very weak peaks at an angle of 43.3721 corresponding to a reflection of (200).…”
Section: (2-3)measurementssupporting
confidence: 92%
See 2 more Smart Citations
“…The results showed that the films were amorphous. This result agrees with Myong et al [12] and with Ayat et al [13]. The XRD pattern showed very weak peaks at an angle of 43.3721 corresponding to a reflection of (200).…”
Section: (2-3)measurementssupporting
confidence: 92%
“…This should be ascribed to Au phase inhibiting the (NiO:WO3) grain growth. It can also be attributed to the fact that the atomic radii of Au particles are less than that of NiO leading to Myong et al [12] and with Ayat et al [13]. The XRD pattern showed very weak peaks at an angle of 43.3721 corresponding to a reflection of (200).…”
Section: (2-3)measurementsmentioning
confidence: 91%
See 1 more Smart Citation
“…1b, the peak seen at 3448 cm-1 may be due to O-H stretching and deformation assigned to the water adsorption on the metal surface. The absorption band observed at 1628 cm -1 Ag − O are due to stretching vibration [25], while the band at 694 cm -1 corresponds to Ag-O interaction [27,28].…”
Section: Ftir Analysismentioning
confidence: 99%
“…The obtained results are well in accordance with a standard ICDD le No: 761393, Which is indexed to the face-centred cubic structure, indicating they have a relatively high degree of crystallinity. In the XRD pattern of the PTh-nAg 2 O polymer nanocomposite, the planes (111) and (110) represent the pointers of silver oxide nanoparticles, and the peaks (211) and ( 220) correspond to the face-centred cubic crystal structure [27,28].…”
Section: Xrd Analysismentioning
confidence: 99%